Perl testing : a developer's notebook - Langworth, Ian (O'Reilly, 2005)
Is there any sexier topic in software development than software testing? That is, besides game programming, 3D graphics, audio, high-performance clustering, cool websites, et cetera? Okay, so software testing is low on the list. And that's unfortunate, because good software testing can increase your productivity, improve your designs, raise your quality, ease your maintenance burdens, and help to satisfy your customers, coworkers, and managers. Perl has a strong history of automated tests. A very early release of Perl 1.0 included a comprehensive test suite, and it's only improved from th.